Factors that Affect Attitude Toward a Retail Web Site - Elliott, Michael T.; Speck, Paul Surgi (Journal of marketing theory and practice, 2005)
As the expectations of online shoppers rise, their satisfaction with online retailers has declined. Using an online shopping scenario, undergraduate marketing students evaluated the effects of six web site factors and two individual difference variables on attitude toward a retail web site. Results indicate that five web site factors (ease of use, product information, entertainment, trust, and currency) affect consumer attitude toward a retail web site. The two individual difference variables (product involvement and online shopping experience) moderate the relationship between specific web site factors and attitude toward a retail web site. These findings suggest that online retailers should emphasize site factors that best suit the involvement/experience profile of their primary users.